Impact of TiO2 and CaCO3 nanoparticles and their incorporation in polysulfone composite membrane on photocatalytic degradation of RB 5 - Arun Isloor; Sneha O; Glanish martis; Satish Bhat; Praveen Mugali (Advances in Environmental Technology)
Contamination of water resources by dyes is a potential peril to humans and the ecosystem. Photocatalytic decomposition is one of the efficient ways to remove hazardous dyes present in water. CaCO3 and TiO2 nanoparticles have been synthesized from calcium chloride and sodium carbonate using a precipitation method and sol-gel technique, respectively. Synthesized CaCO3 and TiO2 nanoparticles were analysed using X-ray diffraction (XRD), ultraviolet visible (UV-Vis) spectroscopy, scanning electron microscopy (SEM), and energy dispersive X-ray spectroscopy (EDX). The experimental results showed that the synthesized CaCO3 nanoparticles were of calcite and the TiO2 nanoparticles of anatase. Polysulfone (PSF) composite membranes embedded with CaCO3 and TiO2 nanoparticles were prepared systematically. These synthesized nanoparticles and their embedded PSF membranes were effectively utilized for the photocatalytic decomposition of the reactive black 5 (RB 5) dye. 88.8% and 23.6% degradation of RB 5 dye was observed for TiO2 and CaCO3 nanoparticles, respectively. However, it was observed that the TiO2 and CaCO3 nanoparticle incorporated PSF membranes showed a lower photodegradation of 60.4% and 18.37%, respectively, due to the masking of the nanoparticles by the polymer matrix. The direct usage of the nanoparticles showed improved photodegradation properties.